Aversion to playing God and moral condemnation of technology and science. (29th April 2019) - Waytz, Adam; Young, Liane
Abstract : This research provides, to our knowledge, the first systematic empirical investigation of people's aversion to playing God . Seven studies validate this construct and show its association with negative moral judgements of science and technology. Motivated by three nationally representative archival datasets that demonstrate this relationship, studies 1 and 2 demonstrate that people condemn scientific procedures they perceive to involve playing God. Studies 3–5 demonstrate that dispositional aversion to playing God corresponds to decreased willingness to fund the National Science Foundation and lower donations to organizations that support novel scientific procedures. Studies 6a and 6b demonstrate that people judge a novel (versus established) scientific practice to involve more playing God and to be more morally unacceptable. Finally, study 7 demonstrates that reminding people of an existing incident of playing God reduces concerns towards scientific practices. Together, these findings provide novel evidence for the impact of people's aversion to playing God on science and policy-related decision-making. This article is part of the theme issue 'From social brains to social robots: applying neurocognitive insights to human–robot interaction'.